Accumulation of cadmium in growing peanut (Arachis hypogaea L.) seedlings - its effect on lipid peroxidation and on the antioxidative enzymes catalase and gualacol peroxidase - Kumar, Sunil; Mehta, Urmil J.; Hazra, Sulekha (Journal of Plant Nutrition and Soil Science, 2008)
In plants exposed to high metal concentrations, mechanisms to counteract the oxidative burst are crucial for its survival. To investigate the temporal sequence of physiological reactions of peanut seedlings (Arachis hypogaea L.) to cadmium exposure, seeds were cultured in increasing concentrations of CdCl(2), ranging from 50 to 300 mu M. Germination frequency was scored, and the distributions of Cd in root, stem, and leaves were determined after 2 and 4 weeks of culture. Lipid peroxidation and activities of antioxidative enzymes including catalase (CAT, EC 1.11.1.6) and guaiacol peroxiclase (GPX; EC 1.11.1.7) were estimated in these three parts of the plant. Germination of seedlings was not affected, but the growth of seedlings was severely suppressed with increasing concentrations of CdCl(2) and incubation period. Pattern of Cd distribution in the three organs varied with concentration and period of exposure to Cd. Increased lipid peroxidation was detected in all parts of the developing seedlings with increasing metal accumulation. Catalase and guaiacol peroxidase activity varied in the three parts of the seedlings with concentration of Cd and incubation period. Guaiacol peroxidase activity appears to be more active in scavenging the reactive oxygen species in developing peanut seedlings. The results of the present experiment demonstrate the advantages of a tissue-culture model system in studying the complex network of interactions of various factors in stress tolerance.
Keywords: Abiotic stress; heavy metal; stress tolerance; TBARS; thiobarbituric acid; Tissue culture